Artificial Radio Illumination in a Closed Space - Dmitriev, A. S.; Itskov, V. V.; Petrosyan, M. M.; Popov, M. G.; Ryzhov, A. I. (Journal of communications technology & electronics, 2019)
The problem of illumination of objects and surfaces by artificial incoherent sources of microwave radiation (radio light lamps based on dynamic chaos generators) in order to observe them using special receiving equipment is considered. A scheme of a receiver is developed and an experimental model of such a receiver with a spatial resolution sufficient for the visualization of a part of the surrounding space in artificial radio light is implemented. Images of a room in radio light are obtained. The feasibility of detecting changes on these images, associated with the emergence of new objects, is shown.